Contribution of Home Industry Activities in Increasing Housewives’ Income - Rahmawati, Rina Puji (IDFoS Indonesia, 2022)
Prambatan Village, Balen Sub-district, Bojonegoro Regency has the potential for a banana debog craft home industry, but currently only makes dry debogs resembling ropes, called